Survival in oral and pharyngeal cancers is catching up with laryngeal cancer in the NORDIC countries through a half century - Zitricky, Frantisek; Koskinen, Anni I; Hemminki, Otto; Försti, Asta; Hemminki, Akseli; Hemminki, Kari (Cancer medicine, 2024)
BACKGROUND: Cancers of the head and neck (HN) are heterogeneous tumors with incidence rates varying globally. In Northern Europe oral and oropharyngeal cancers are the most common individual types. Survival for HN varies by individual tumor type but for most of them survival trends are not well known over extended periods of time. METHODS: Data for a retrospective survival study were obtained for Danish, Finnish, Norwegian, and Swedish patients from the NORDCAN database from 1971 to 2020. Relative 1- and 5-year survival rates and 5/1-year conditional survival for years 2-5 were calculated. RESULTS: Both 1- and 5-year survival improved for all HN cancers but only marginally for laryngeal cancer. For the other cancers a 50-year increase in 5-year survival was about 30% units for nasopharyngeal and oropharyngeal cancers, 20% units for oral cancer and somewhat less for hypopharyngeal cancer. CONCLUSIONS: 5-year survival reached about 65% for all HN cancers, except for hypopharyngeal cancer (30%). Human papilloma virus infection is becoming a dominant risk factor for the rapidly increasing oropharyngeal cancer, the prevention of which needs to emphasize oral sex as a route of infection.
Keywords: Female; nádory hltanu; ženské pohlaví; pharyngeal cancer; Pharyngeal Neoplasms; Scandinavian and Nordic Countries; lidé; Laryngeal Neoplasms; Mouth Neoplasms; míra přežití; nádory hrtanu; Risk Factors; Incidence; retrospektivní studie; nádory úst; Male; incidence; Aged; human papilloma virus; rizikové faktory; Skandinávie a severské státy; Survival Rate; lidé středního věku; oral cancer; senioři; mužské pohlaví; conditional survival; Retrospective Studies; Middle Aged; Humans